Perencanaan Penggantian Komponen Generator Listrik Daya 2,5 kW - Reza Nandhika Putra Wijaya; Syamsul Hadi; Mochammad Reza Maulana Ramadhon; Bintang Erlangga; Yohan Nur Azizi; Hallan Shandria Rifqi (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
The problem with a 4-stroke gasoline engine-driven electric generator is a decrease in tool performance due to wear on important components for the stator, cooling fan, air filter, oil filter, and gasket. The purpose of component replacement planning is to obtain replacement costs, maintenance schedules in 2027, and the ratio of maintenance costs to profits. The component replacement planning method includes collecting maintenance data from previous years, applying the inspection-replace-repair-overhaul (IRRO) method, assessing component conditions, predicting component lifespan, predicting labor costs, predicting supporting equipment to be used in maintenance, predicting spare part replacement times, predicting maintenance costs in 2027, and calculating the ratio of maintenance costs to profits. The results of the replacement planning obtained maintenance costs in 2027 amounting to IDR 570,007,- with an estimated electric generator rental rate of IDR 30,000,-/hour which has the potential to be rented for 128 hours/year, a profit of IDR 3,840,000,- was obtained, and the ratio of maintenance costs to profits was 14.84% which implies that a 2.5 kW electric generator that uses gasoline-pertalite fuel of around 1.5 liters/hour at maximum power is still suitable for use in the next few years and has the potential to generate profits.